2-D PAGE Map Analysis: Methods and Protocols - Marengo, Emilio; Robotti, Elisa (Methods in molecular biology, 2016)
Sources of Experimental Variation in 2D-Maps: The Importance of Experimental Design in Gel-Based Proteomics.- Decoding 2D-Maps by Autocovariance Functions.- Two-Dimensional Gel Electrophoresis Image Analysis via Dedicated Software Packages -- Comparative Evaluation of Software Features and Performances.- Image Pretreatment Tools I: Algorithms for Maps Denoising and Background Subtraction Methods.- Image Pretreatment Tools II: Normalization Techniques for 2DE and 2D-DIGE.- Spot Matching of 2-DE Images Using Distance, Intensity, and Pattern Information -- Algorithms for Warping of 2D-PAGE Maps.- 2-DE Gel Analysis: The Spot Detection.- GENOCOP Algorithm and Hierarchical Grid Transformation for Image Warping of Two Dimensional Gel Electrophoretic Maps.- Detection and Quantification of Protein Spots by Pinnacle.- A Novel Gaussian Extrapolation Approach for 2D Gel Electrophoresis Saturated Protein Spots.- Multiple Testing and Pattern Recognition in 2DE Proteomics.- Chemometric Multivariate Tools for Candidate Biomarkers Identification: LDA, PLS-DA, SIMCA, Ranking-PCA.- The Use of Legendre and Zernike Moment Functions for the Comparison of 2D-PAGE Maps.- Nonlinear Dimensionality Reduction by Minimum Curvilinearity for Unsupervised Discovery of Patterns in Multidimensional Proteomic Data.- Differential Analysis of 2D-Maps by Pixel-Based Approaches.